Why the Increasing Trend of Summer Rainfall over North China Has Halted since the Mid-1990s. (27th January 2020) - Liu, Haiwen; Miao, Jiarui; Wu, Kaijun; Du, Mengxing; Zhu, Yuxiang; Hou, Shaoyu
Abstract : Previous studies indicate that the summer (July-August) rainfall over North China has decreased since the mid-1970s due to the weakening of East Asian summer monsoon (EASM). However, this study firstly discovers the new evidences that the summer rainfall over North China had a significant increasing tendency during 1979–1996; since 1997, this increasing tendency has halted while more summer droughts occurred over North China. One important cause for the halted increasing tendency over North China is the interdecadal decrease of the westerly water vapor transport during 1997–2016 in addition to the weakened EASM. The decrease of the westerly water vapor transport during 1997–2016 was due to the interdecadal warming over Lake Baikal. The interdecadal warming in the upper troposphere at 200 hPa forced the weakening of the upper-level zonal winds since 1997, which resulted in the anomalous descending flow over the north side of North China and the halted precipitation trend in North China.